DIGITAL TOOLS IN ACQUISITION OF THEMES ABOUT ETHNICALLY VARIED CULTURE ENVIRONMENT OF LATGALE - Senkāne, Olga; Laganovska, Karīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The object of the particular research is involvement of students in informative stockbuilding of a regional museum during research practice. The aim of the research is to carry out evaluation of this form of involvement and its advantages: using discourse analysis (Jean Liotard); putting forward particular indicators; as well as applying several communication theories (Nikolai Nikishin, Yuri Lotman, Peter van Mensch); and regarding virtual museum as a special communication system based on non-verbal communication of visitors with exhibits. Possible benefits of the museum in this evaluation are of minor importance. The most significant aspect is to reveal student's (museum employee’s during the research practice) as 'sender’s' role in cognition and non-verbal communication with the addressee or the museum visitor. It is demonstrated in coordinated and still independent work, frequently oriented towards self-initiative, creative solutions based on particular knowledge and simultaneously initiating acquisition of new information, as well as promoting development of skills. These skills include communicating with an interviewee; carrying out content analysis of media text, identifying features of stereotypical thinking; creating brief but still informatively capacious description of an exhibit. The use of digital tools during the study process is completely related to scientific activities of academic staff in the implementation of research projects oriented towards innovations as well as provision of stable feedback. If the research is carried out in tight relationship of scientists and students; everyone wins: students help academic staff (thus create conditions for their own research), carry out creative work, make own discoveries, because materials necessary for research are already collected and accordingly supplied; while academic staff develops students' professional competences by coordinating practical work, following their theoretical knowledge, skills and abilities, promoting creative solutions and thus educate new generation of scientists tempered in performing preparatory actions and open for innovations, elaboration and implementation of own creative research projects.